Measurement of the 244Cm and 246Cm neutron-induced capture cross sections at the n_TOF facility - Alcayne V.; Kimura A.; Mendoza E.; Cano-Ott D.; Martínez T.; Aberle O.; Andrzejewski J.; Audouin L.; Bécares V.; Bacak M.; Barbagallo M.; Becčvář F.; et al. (EPJ Web of Conferences, 2019)
The neutron capture reactions of the 244Cm and 246Cm isotopes open the path for the formation of heavier Cm isotopes and heavier elements such as Bk and Cf in a nuclear reactor. In addition, both isotopes belong to the minor actinides with a large contribution to the decay heat and to the neutron emission in irradiated fuels. There are only two previous 244Cm and 246Cm capture cross section measurements: one in 1969 using a nuclear explosion [1] and the most recent data measured at J-PARC in 2010 [2]. The data for both isotopes are very scarce due to the difficulties in performing the measurements: high intrinsic activity of the samples and limited facilities capable of providing isotopically enriched samples. We have measured both neutron capture cross sections at the n_TOF Experimental Area 2 (EAR-2) with three C6 D6 detectors and also at Area 1 (EAR-1) with the TAC. Preliminary results assessing the quality and limitations (back-ground subtraction, measurement technique and counting statistics) of this new experimental datasets are presented and discussed.